Pola Asuh Dengan Terjadinya Picky Eater (Pilih-Pilih Makanan) Pada Anak Usia 3-6 Tahun Di Dusun Sumberaji Desa Karangjeruk Kecamatan Jatirejo Kabupaten Mojokerto - Rufaida, Zulfa; Lestari, Sri Wardini Puji (Journal of Issues in Midwifery, 2018)
Picky eater is a child's behavior is unwilling or refuses to eat, or have difficulty consuming the food. Picky eater influenced by upbringing, feeding behavior of parents, the mother and child interaction, exclusive breastfeeding, solids, and psychological and physical condition of the child. Picky eater can cause children micro- and macronutrient deficiencies that ultimately interfere with the physical and psychological growth. The aim of research to determine the relationship of parenting parents against the picky eater in children aged 3-6 yearsThe study design cross sectional observational analytic types. Population mothers of children aged 3-6 years in Dusun Sumberaji Desa Karangjeruk Kecamatan Jatirejo Kabupaten Mojokerto. Sample 41 respondents drawn using sampling techniques Non – Probability sampling, kind of total sampling. Retrieval of data held on December 18th 2017 – January 05th 2018, the research instruments using a questionnaire with interview techniques. Data analysis used Fisher exact test, α = 0.05.The results showed that the average of respondent who had democratic parenting style was as many as 22 respondents (64.7%) with a child who experienced picky eater.Results count the Fisher exact test test obtained exact sig value (2-sided) 0.401 meant that Ho accepted,there is no relationship between parenting style of parenst to theincidentof picky eater in children used 3-6 years.Conclusions democratic parenting style adopted by parents still can not make children become picky eater so it needs to pay attention to the physical condition of the child. Parents are expected to vary the diet so that children are more interested in eating food.Keywords: Parenting, Picky Eater